(untitled) (Nepal Medical College Journal, 2020)
Various studies have shown that abnormal body mass index (BMI) of an individual is linked to poor sleep. Abnormal BMI is a predisposing factor for many non- communicable diseases like cardiovascular diseases and diabetes. However, if BMI is affected by sleep, detecting sleep abnormality followed by simple corrective measures may help in making BMI normal hence preventing the risk of many such diseases. Using Asian Classification for BMI and questions from Pittsburgh Sleep Quality Index (PQSI) a survey was carried out among persons aged 15 to 60 years in a ward of Gokarneshwor Municipality. In this study, out of a total of 563 persons 4.4% were underweight, 33.9% had normal BMI, 18.5% were overweight and 43.2% were obese. Around 22% reported a reduced duration of sleep but only around 5% of the persons felt that their quality of sleep was poor. This study showed that the association between reduced sleep duration and abnormal BMI was significant even when confounding variables like tobacco or alcohol and poverty state were removed.